The contribution of EU b-solutions initiative to foster soft and hard territorial governance and how to assess its main cross-border impacts in the EU cross-border regions - Medeiros, E. (Journal of Advanced Studies on Borders, Cooperation and Development, 2024)
Territorial governance is embodied by rules and norms and implemented through hard (laws, planning designs and strategies, etc.) and soft (ways of decision-making, participation, co-creation, capacity building, etc.) related processes (Kaufmann & Kraay, 2007). These are related and affected by the European Union (EU) b-solutions initiative (Medeiros et al. 2024) adopted by the European Commission (EC) on 20 September 2017